2009
DOI: 10.1007/s10646-009-0446-7
|View full text |Cite
|
Sign up to set email alerts
|

New evidences of Roundup® (glyphosate formulation) impact on the periphyton community and the water quality of freshwater ecosystems

Abstract: Argentina is the second largest world producer of soybeans (after the USA) and along with the increase in planted surface and production in the country, glyphosate consumption has grown in the same way. We investigated the effects of Roundup (glyphosate formulation) on the periphyton colonization. The experiment was carried out over 42 days in ten outdoor mesocosms of different typology: "clear" waters with aquatic macrophytes and/or metaphyton and "turbid" waters with great occurrence of phytoplankton or susp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
121
2
20

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 196 publications
(156 citation statements)
references
References 41 publications
13
121
2
20
Order By: Relevance
“…A recent concern is that glyphosate (along with other herbicide active ingredients dicamba and 2,4-D), as well as common surfactants (Tween80, carboxymethyl cellulose) at or below recommended application concentrations can change the susceptibility of bacteria to a diverse range of antibiotics (ampicillin, chloramphenicol, ciprofloxacin, kanamycin, tetracycline) upon concurrent exposure, and thus, glyphosate may serve as one of the drivers for antibiotic resistance (Kurenbach et al, 2017;Van Bruggen et al, 2018). As indicated, through water pollution its formulations can disturb aquatic ecosystems (Vera et al, 2010;Perez et al, 2011) including fish (Jofré et al, 2013). Removal or degradation of glyphosate residues from raw drinking water by bank filtration may not be efficient, but oxidants used in water treatment (e.g., Cl 2 or O 3 ) were shown to be effective in degrading their concentration below the EU drinking water threshold level of 0.1 µg/l (Jönsson et al, 2013).…”
Section: Exposure To Glyphosate-environmental and Food Analysis Humamentioning
confidence: 99%
“…A recent concern is that glyphosate (along with other herbicide active ingredients dicamba and 2,4-D), as well as common surfactants (Tween80, carboxymethyl cellulose) at or below recommended application concentrations can change the susceptibility of bacteria to a diverse range of antibiotics (ampicillin, chloramphenicol, ciprofloxacin, kanamycin, tetracycline) upon concurrent exposure, and thus, glyphosate may serve as one of the drivers for antibiotic resistance (Kurenbach et al, 2017;Van Bruggen et al, 2018). As indicated, through water pollution its formulations can disturb aquatic ecosystems (Vera et al, 2010;Perez et al, 2011) including fish (Jofré et al, 2013). Removal or degradation of glyphosate residues from raw drinking water by bank filtration may not be efficient, but oxidants used in water treatment (e.g., Cl 2 or O 3 ) were shown to be effective in degrading their concentration below the EU drinking water threshold level of 0.1 µg/l (Jönsson et al, 2013).…”
Section: Exposure To Glyphosate-environmental and Food Analysis Humamentioning
confidence: 99%
“…These methods can also be used to identify the temporary, progressive or persistent effects of contaminants on communities (Rand et al, 2000;Belanger et al, 2002), by measuring their resilience, and also to distinguish between the direct and indirect ecological effects of disturbances caused by contaminants (Belanger et al, 2000;Culp et al, 2000;Hense et al, 2003). Just to provide recent examples of the variety of systems used, 3L liter Pyrex Erlenmeyer flasks have been used to study the response of microbial communities following exposure to glyphosate (Pesce et al, 2009a), indoor experimental channels have been used to study the combined effect of physical factors and exposure to diuron on benthic microbial communities (Villeneuve, 2008), and artificial outdoor mesocosms (surface area 25 m 2 ) have been used by Vera et al (2010) to evaluate the impact of Roundup on periphyton communities.…”
Section: Microcosms Mesocosms and Macrocosmsmentioning
confidence: 99%
“…For example, Dorigo et al (2007) found that there were changes in the composition of microbial communities in a small river displaying an upstream-downstream pollution gradient, and that species located in the polluted downstream area were more tolerant towards herbicides than those located in the upstreamunpolluted area. Recently, Vera et al (2010) have shown that diatoms were more susceptible than cyanobacteria to glyphosate in periphyton communities, and consequently that over the long term a shift occurred in the composition of these communities. In the same way, Lürling & Roessink (2006) showed, by an experimental approach, that Scenedesmus (green algae) out competed Microcystis (Cyanobacteria) in the absence of metribuzin, a photosynthesis-inhibiting herbicide, whereas the reverse was true in the presence of this herbicide.…”
Section: Impact Of Herbicides On the Composition And Structure Of Frementioning
confidence: 99%
See 1 more Smart Citation
“…Comparable results were obtained by Pesce et al (2009), reporting changes in riverine algal communities exposed to about 10 μg/L of glyphosate alone, in a microcosms experiment. In addition, mesocosms studies showed remarkable results with a single pulse application of Roundup ® at concentrations of 6 and 8 mg a.i./L (Pérez et al, 2007;Vera et al, 2010). Even if these two contributions assessed herbicide effects in worst case scenarios, glyphosate concentration at the end of the experiments (11 and 14 days respectively), were around 2 mg a.i./L and effects were still clearly observed.…”
Section: Effects On Non-target Aquatic Plants and Algaementioning
confidence: 97%